UJI AKTIVITAS ANTIBAKTERI EKTRAK ETANOL TIGA VARIETAS BIJI PEPAYA (Carica papaya L) TERHADAP BAKTERI Staphylococcus aureus, Staphylococcus epidermidis DAN Propionibacterium acnes - Emma - Susanti (LPPM Universitas Abdurrab, 2021)
The seeds of papaya (Carica papaya L) can be used as traditional medicine. The first test of ethanol extract of papaya seeds obtained in the form of terpenoids and saponins. In Pekanbaru, there are three varieties of papaya, papaya callina, papaya honey and papaya palas. This research aims to determine the antibacterial activity of ethanol extract of three varieties of papaya seeds (Carica papaya L) against Staphylococcus aureus, Staphylococcus epidermidis and Propionibacterium acnes bacteria with disc diffusion method. Test results of ethanol extract of papaya varieties callina with the highest at concentration 80% inhibitory zone Staphylococcus epidermidis was 19.83 mm. Ethanol extract of papaya seeds varieties honey gave the highest inhibitory zone in Staphyloccous aureus at concentration 80% was 19,85 mm. While papaya seeds varieties palas gave the highest inhibitory zone in Staphylococcus epidermidis at concentration 80% was 19.70 mm. The variety that gives the highest inhibitory zone is the ethanol extract of papaya callina seeds on the Staphylococcus epidermidis